The Impact of Liquid Adjunct and Barley on Wort and Beer Quality - Yano, Masaaki; Back, Werner; Krottenthaler, Martin (BrewingScience, 2008)
The use of adjunct is one of the most important factors in the beer industry, since adjunct not only influences production variables such as quality and cost, but also has an influence on market sales strategy, such as pricing strategy in Japan where liquor tax is assessed according to malt usage. Although a great deal of knowledge has been accumulated regarding adjuncts such as liquid adjunct (L. A.) and barley, not many reports have been published regarding special quality characteristics derived from these adjuncts, such as beer flavor stability. In this study, we have performed exhaustive research to elucidate the impact of L. A. and barley on process and quality, specifically with regard to taste and flavor stability, by comparing wort and beer made from 100 % malt, 75 % malt with 25 % adjunct, and 60 % malt with 40 % adjunct, using a pilot plant capable of making 60 L of cold wort. No exogenous enzymes were used in the brews. As a result of our experiments, we discovered a tendency toward improved flavor stability when 40% of malt was substituted for L. A. We also found a tendency that flavor stability decreased when 40 % of malt was substituted for barley. Other process and quality characteristics of adjunct beers are also discussed as well.